The evaluation of workers by customers as a method of control and monitoring in firms: Digital reputation and the European Union's General Data Protection Regulation. - TODOLÍ‐SIGNES, Adrián (International Labour Review, 2021)
As a method of surveillance and monitoring, the evaluation of workers by customers and employers and the disclosure of the results pose a series of challenges for the current legal framework of the European Union (EU). Employees subject to such evaluations are exposed to a far more intense and wider degree of monitoring of their work than traditional workers. The phenomenon arises from the adoption of a customer perspective, seeking to make work observable at all times, without any cost to firms. In this light, the author analyses the EU's General Data Protection Regulation, which establishes very specific restrictions when requesting and disclosing information about workers.